Lithium ion battery
By using a specific non-aqueous electrolyte composition and the specific surface area and porosity range of the positive electrode material layer in lithium-ion batteries, an organic matter protection film is generated, which solves the problems of deterioration in performance of lithium iron phosphate positive electrode batteries and poor fast charging and circulation performance at high temperatures, and improves high-temperature storage performance and fast charging and circulation performance.
Patent Information
- Application Number
- CN202510206470.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-25
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2045-02-25
AI Technical Summary
The existing lithium iron phosphate positive electrode battery has deteriorated performance and poor fast charging and circulation performance at high temperatures.
The non-aqueous electrolyte is used, including at least one compound 1 to 5 as the first additive, fluorovinyl carbonate as the second additive, and the short-chain carboxylic acid ester-based compound represented by the structural formula 1 as the solvent, and the specific surface area and porosity of the positive electrode material layer are defined within a specific range to form an organic matter protective film to prevent side reactions between the negative electrode and the carboxylic acid ester.
It significantly improves the high-temperature storage performance and fast charging and circulation performance of lithium-ion batteries, avoids the deterioration of the battery's performance at high temperatures, and improves the market competitiveness of the battery.
Smart Images

Figure SMS_21 
Figure SMS_22 
Figure SMS_23
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium ion batteries and relates to a lithium ion battery, and in particular to a lithium ion battery with excellent high temperature performance and fast charging cycle performance. Background Art
[0002] At present, the new energy vehicle industry is booming, and the market demand for power lithium-ion batteries is high. The two types of cathode materials commonly used in commercial power lithium-ion batteries are ternary nickel cobalt manganese oxide materials and phosphate materials represented by lithium iron phosphate. Compared with ternary materials, the advantages of phosphate materials are long cycle life, low cost, and high safety performance, but their disadvantages are low energy density and poor rate performance. If the rate performance of lithium iron phosphate cathode batteries can be improved to meet consumers' demand for fast charging of electric vehicles, the market competitiveness of lithium iron phosphate cathode batteries can be enhanced. The common method in the industry is to use low-viscosity carboxylates as electrolyte solvents to reduce the transmission resistance of lithium ions during high-rate charging and reduce the battery polarization internal resistance to improve the rate performance of lithium iron phosphate cathode batteries. However, the defect of carboxylates is that they are easy to react with the negative electrode in a highly lithium-embedded state at high temperatures, resulting in performance degradation at high temperatures. Therefore, how to balance the high temperature performance and fast charging cycle performance of lithium iron phosphate cathode batteries is a research direction that has received much attention. Summary of the invention
[0003] Based on this, the purpose of the present invention is to provide a lithium-ion battery to solve the problems of performance degradation and poor fast charging cycle performance of lithium iron phosphate positive battery at high temperature in the prior art.
[0004] To achieve the above object, the present invention adopts the following technical solution.
[0005] The present invention provides a lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet and a non-aqueous electrolyte; The positive electrode sheet includes a positive electrode material layer, the positive electrode material layer includes a positive electrode active material, and the positive electrode active material includes a phosphate compound LiFe 1-x-y Mn x M y PO4, wherein 0≤x≤0.8, 0≤y≤0.05, and M includes any one or more of Co, B, Ga, F, W, Zr, Mg, Na, Pb, K, Al, Cr, Ba, Ca, Ni, Sr, Ti, Zn, Si, V, Mo, or Nb; The non-aqueous electrolyte comprises a first additive, a second additive, a lithium salt and a solvent; the first additive comprises at least one of the following compounds: Compound 1 Compound 2 Compound 3 Compound 4 Compound 5; The second additive includes fluoroethylene carbonate; The solvent includes a compound shown in structural formula 1; ; Structural formula 1 Wherein, R1 is an alkyl group with a carbon number of ≤2, R2 is an alkyl group with a carbon number of ≤3, the hydrogen atoms in R1 may be partially replaced by fluorine atoms, and the total number of carbon atoms in R1 and R2 is ≤4; The lithium-ion battery meets the following conditions: 0.3≤0.01×(c+e+5d) / (a+b)≤20, 0.01≤a≤3, 0.05≤b≤1.5, 30≤c≤50, 6≤d≤12, 10≤e≤35; Wherein, a is the mass percentage of the first additive in the non-aqueous electrolyte, in units of %; b is the mass percentage of the second additive in the non-aqueous electrolyte, in %; c is the mass percentage of the compound represented by structural formula 1 in the non-aqueous electrolyte, in units of %; d is the specific surface area of the positive electrode material layer, in m 2 / g; e is the porosity of the positive electrode material layer, in %.
[0006] In the field of power lithium-ion batteries, phosphate cathodes represented by lithium iron phosphate have the advantages of longer cycle life, better safety, and higher cost performance compared to nickel-cobalt-manganese ternary cathodes, but phosphate cathodes have poor rate performance, mainly due to their poor conductivity. If the rate performance of lithium iron phosphate cathode batteries can be improved, it can make up for the gap with ternary cathodes to a certain extent and be more competitive in the market.
[0007] The lithium ion battery provided in the present invention uses at least one compound selected from Compounds 1 to 5 as a first additive, fluoroethylene carbonate as a second additive, and a compound represented by Structural Formula 1 as a solvent. The inventors have found through extensive research that when the mass percentage of the first additive in the electrolyte is a%, the mass percentage of the second additive in the electrolyte is b%, the mass percentage of the compound represented by Structural Formula 1 in the non-aqueous electrolyte is c%, and the specific surface area dm of the positive electrode material layer is 2 / g and the porosity e% of the positive electrode material layer satisfy the relationship 0.3≤0.01×(c+e+5d) / (a+b)≤20, 0.01≤a≤3, 0.05≤b≤1.5, 30≤c≤50, 6≤d≤12, 10≤e≤35, and a lithium-ion battery with excellent high-temperature storage performance and fast-charge cycle performance can be obtained. The reason is speculated that, on the one hand, from the perspective of non-aqueous electrolytes, one of the main factors limiting the fast charging of batteries is the ionic conductivity of the electrolyte. Short-chain carboxylic acid ester solvents have lower viscosity, can reduce the resistance to the movement of lithium ions, and can significantly improve the ionic conductivity of the electrolyte, but the defect of short-chain carboxylic acid ester solvents is poor electrochemical stability. At high temperatures, they are prone to side reactions with the negative electrode in a highly lithium-embedded state, resulting in degradation of high-temperature storage and high-temperature cycle performance. The combined use of the first additive and the second additive can form an organic protective film on the surface of the negative electrode, which can prevent the negative electrode from reacting with the carboxylic acid ester, avoid the carboxylic acid ester from deteriorating the high temperature performance of the battery, and have a lower interfacial internal resistance, which is beneficial to further improve the fast charge cycle performance of the battery. On the other hand, by limiting the specific surface area and porosity of the positive electrode material layer within a certain range, the lithium ion transmission and charge transfer efficiency at the electrode-electrolyte interface are improved, thereby improving the fast charge cycle performance of the battery. In summary, in the present invention, by limiting the content of the first additive in the non-aqueous electrolyte, the content of the second additive, the content of the compound shown in structural formula 1, and the specific surface area of the positive electrode material layer and the porosity of the positive electrode material layer within a certain range, the various parameters achieve a synergistic effect, thereby obtaining a lithium ion battery with excellent high temperature storage performance and fast charge cycle performance. Preferably, the lithium ion battery satisfies: 0.5≤0.01×(c+e+5d) / (a+b)≤10.
[0008] In a non-aqueous electrolyte, at least one of compounds 1 to 5 is used as a first additive in combination with fluoroethylene carbonate (FEC) as a second additive. During the battery formation process, a reduction reaction occurs on the surface of the negative electrode, wherein the first additive can generate a dense and thin organic protective film with certain flexibility through a ring-opening polymerization reaction, and FEC introduces inorganic salt substances such as LiF with high ion conduction efficiency and strong thermal stability into the protective film. This negative electrode protective film can prevent the negative electrode from having side reactions with carboxylic acid esters, thereby preventing carboxylic acid esters from deteriorating the high temperature performance of the battery. When the mass percentage a% of the first additive in the non-aqueous electrolyte is too small, that is, a%<0.01%, a dense interface film that completely covers the surface of the negative electrode cannot be generated, and the negative electrode cannot be protected; when the mass percentage a% of the first additive in the non-aqueous electrolyte is too high, that is, a%>3%, the generated protective film layer is thicker, and the interface impedance of the battery cell increases synchronously, which is not conducive to the rate performance of the battery, and more Joule heat will be generated, which is too serious for high temperature storage. Specifically, the mass percentage a% of the first additive in the non-aqueous electrolyte is 0.01%, 0.03%, 0.05%, 0.07%, 0.09%, 1%, 1.3%, 1.5%, 1.7%, 1.9%, 2.0%, 2.3%, 2.5%, 2.7%, 3%, or a range consisting of any two of these values. Preferably, the mass percentage a% of the first additive in the non-aqueous electrolyte is 0.05% to 1%.
[0009] When the mass percentage b% of the second additive is too little, that is, b%<0.05%, a dense interface film that completely covers the surface of the negative electrode cannot be generated, and the protective effect is insufficient; when the mass percentage b% of the second additive is too high, that is, b%>1%, the interface film will be too thick, resulting in an increase in the internal resistance of the battery and deterioration of the cycle performance. Specifically, the mass percentage b% of the second additive in the total non-aqueous electrolyte is 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5% or a range consisting of any two of these values. Preferably, the mass percentage b% of the second additive in the non-aqueous electrolyte is 0.1%~1%.
[0010] In a non-aqueous electrolyte, the short-chain carboxylic acid ester shown in structural formula 1 is used as a solvent, has a low viscosity, can reduce the resistance to the movement of lithium ions, can significantly improve the ionic conductivity of the electrolyte, and improve the fast charging cycle performance of the battery. When the mass percentage c% of the solvent is too small, that is, c%<30%, it cannot significantly reduce the viscosity; if the mass percentage c% of the solvent is too high, that is, c%>50%, the degradation for high temperature storage is too serious. Specifically, the mass percentage c% of the solvent is 30%, 32%, 34%, 36%, 38%, 40%, 42%, 44%, 46%, 48%, 50% or a range consisting of any two of these values. Preferably, the mass percentage c% of the solvent in the non-aqueous electrolyte is 30%~45%.
[0011] From the perspective of the electrode, the main factor limiting the rapid charging of the battery is the limited transmission of lithium ions across the phase boundary at the electrode-electrolyte interface. By limiting the specific surface area of the positive electrode material layer to a suitable range, the contact area between the electrolyte and the electrode can be increased. 2 / g is too small, that is, dm 2 / g<6 m 2 / g, it is not conducive to the fast charging performance of the battery; when the specific surface area of the positive electrode material layer is dm 2 / g is too large, that is, dm 2 / g>12 m 2 / g, it will cause excessive consumption of additives and lithium salts to form the negative electrode protective film during the battery formation process, resulting in an increase in the irreversible capacity of the first charge and deterioration of the first charge and discharge efficiency of the battery. Specifically, the specific surface area of the positive electrode material layer is dm 2 / g is 6 m 2 / g, 7 m 2 / g, 8 m 2 / g, 9 m 2 / g, 10 m 2 / g, 11 m 2 / g, 12 m 2 / g or a range consisting of any two of these values. Preferably, the specific surface area dm 2 / g is 7 m 2 / g~10m 2 / g.
[0012] Specifically, in some embodiments of the present invention, the specific surface area of the positive electrode material layer is tested using the following method: (1) the positive electrode sheet is taken out after the battery is disassembled, and the positive electrode sheet is soaked and cleaned with EMC (ethyl methyl carbonate), vacuum dried for 24 hours, and the positive electrode material layer is scraped off from the positive electrode current collector into powder, and then a small amount of EMC is added to the powder and dispersed using an ultrasonic device, and then the powder is dried and loaded into a sample tube; (2) the sample tube is loaded into a degassing station, and the sample is heated and vacuum degassed to remove the surface adsorbed gas, and the quality is tested. The sample is subjected to adsorption and desorption test using a specific surface area analyzer, and the specific surface area of the positive electrode material layer is calculated from the measured adsorption isotherm.
[0013] The porosity of the positive electrode material layer is related to the adsorption and infiltration of the electrode to the electrolyte. Limiting the porosity of the positive electrode material layer within a suitable range is conducive to the adsorption and infiltration of the electrode to the electrolyte, and improving the liquid retention of the battery. When the porosity e% of the positive electrode material layer is too small, that is, e%<10%, it is not conducive to the fast charging performance of the battery; when the porosity e% of the positive electrode material layer is too large, that is, e%>35%, it will lead to a decrease in the active material load, a decrease in the surface density of the electrode, and deterioration of the energy density. Specifically, the porosity e% of the positive electrode material layer is 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35% or a range consisting of any two of these values. Preferably, the porosity e% of the positive electrode material layer is 10% to 30%. More preferably, the porosity e% of the positive electrode material layer is 15% to 25%.
[0014] Specifically, in some embodiments of the present invention, the following method is used to test the porosity of the positive electrode material layer: (1) After disassembling the battery, take out the positive electrode sheet, use EMC to soak and clean the positive electrode sheet, and vacuum dry it for 24 hours. Cut the electrode sheet sample into thin strips of a certain size, measure the apparent volume of the positive electrode material layer, and then load it into the sample tube; (2) Load the sample tube into the degassing station, heat and vacuum degas the sample to remove the surface adsorbed gas, and test the quality. The pore volume of the sample is measured by a mercury intrusion tester, and the porosity (%) = pore volume / apparent volume × 100%.
[0015] Specifically, in some embodiments of the present invention, the compound represented by the structural formula 1 includes at least one of the following compounds 1-1 to 1-6: Compound 1-1 Compound 1-2 Compound 1-3 Compound 1-4 Compound 1-5 Compounds 1-6.
[0016] Preferably, the compound shown in the structural formula 1 includes at least one of compound 1-1, compound 1-2 or compound-5, that is, at least one of methyl acetate, ethyl acetate, or ethyl propionate. More preferably, the compound shown in the structural formula 1 includes at least ethyl acetate. Compared with other carboxylate compounds, ethyl acetate not only has a lower viscosity, can reduce the resistance to the movement of lithium ions, help to improve the ionic conductivity of the electrolyte, but also is beneficial to stabilize the positive electrode structure. Therefore, while improving the fast charging performance of lithium-ion batteries, it can also improve its high temperature performance at the same time, thereby improving the overall performance of electrochemical devices.
[0017] Specifically, in some embodiments of the present invention, the positive electrode active material includes: LiFePO4, LiFe 0.6 Mn 0.4 PO4、LiFe 0.5 Mn 0.5 PO4、LiFe 0.2 Mn 0.8 PO4、LiFe 0.4 Mn 0.6 PO4、LiFe 0.4 Mn 0.55 Zr 0.05 PO4、LiFe 0.4 Mn 0.55 Mg 0.05 PO4、LiFe 0.4 Mn 0.55 Na 0.05 PO4、LiFe 0.4 Mn 0.55 Zn 0.05 PO4、LiFe 0.4 Mn 0.55 Al 0.05 PO4、LiFe 0.4 Mn 0.55 Co 0.05 PO4、LiFe 0.4 Mn 0.55 B 0.05 PO4、LiFe 0.4 Mn 0.55 Ga 0.05 PO4、LiFe 0.4 Mn 0.55 F0.05 PO4、LiFe 0.4 Mn 0.55 W 0.05 PO4、LiFe 0.4 Mn 0.55 Pb 0.05 PO4、LiFe 0.4 Mn 0.55 K 0.05 PO4、LiFe 0.4 Mn 0.55 Cr 0.05 PO4、LiFe 0.4 Mn 0.55 Ba 0.05 PO4、LiFe 0.4 Mn 0.55 Ca 0.05 PO4、LiFe 0.4 Mn 0.55 Ni 0.05 PO4、LiFe 0.4 Mn 0.55 Sr 0.05 PO4、LiFe 0.4 Mn 0.55 Ti 0.05 PO4、LiFe 0.4 Mn 0.55 Si 0.05 PO4、LiFe 0.4 Mn 0.55 V 0.05 PO4、LiFe 0.4 Mn 0.55 Mo 0.05 PO4 or LiFe 0.4 Mn 0.55 Nb 0.05 Any one or more of PO4.
[0018] Specifically, in some embodiments of the present invention, the positive electrode sheet further includes a positive electrode current collector, the positive electrode material layer is located on both sides of the positive electrode current collector, and the positive electrode current collector includes a metal material that can conduct electrons. Preferably, the positive electrode current collector includes one or more of aluminum, nickel, tin, copper, and stainless steel.
[0019] Specifically, in some embodiments of the present invention, the positive electrode sheet further includes a positive electrode binder and a positive electrode conductor. The positive electrode binder includes polyvinylidene fluoride, a copolymer of vinylidene fluoride, polytetrafluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene, a copolymer of tetrafluoroethylene-hexafluoropropylene, a copolymer of tetrafluoroethylene-perfluoroalkyl vinyl ether, a copolymer of ethylene-tetrafluoroethylene, a copolymer of vinylidene fluoride-tetrafluoroethylene, a copolymer of vinylidene fluoride-trifluoroethylene, a copolymer of vinylidene fluoride-trichloroethylene, a copolymer of vinylidene fluoride-fluoroethylene, a copolymer of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, a thermoplastic resin such as thermoplastic polyimide, polyethylene and polypropylene; an acrylic resin; and one or more of styrene butadiene rubber. The positive electrode conductor includes one or more of conductive carbon black, conductive carbon balls, conductive graphite, conductive carbon fibers, carbon nanotubes, graphene, or reduced graphene oxide.
[0020] Specifically, in some embodiments of the present invention, the non-aqueous electrolyte further includes an auxiliary additive, and the auxiliary additive includes at least one of a cyclic sulfate compound, a sultone compound, a cyclic carbonate compound, a phosphate compound, and a borate compound. Adding the auxiliary additive to the electrolyte can participate in the film-forming effect in the formation process together with the first additive and the second additive, further improving the stability of the protective film, thereby further improving the high temperature storage performance and fast charge cycle performance of the battery.
[0021] In some preferred embodiments, the cyclic sulfate ester compound includes at least one of 4-methylvinyl sulfate, vinyl sulfate, and propylene sulfate.
[0022] In some preferred embodiments, the sultone compound includes at least one of 1,3-propane sultone, 1,4-butane sultone, and propenyl-1,3-sultone.
[0023] In some preferred embodiments, the cyclic carbonate compound includes at least one of vinylene carbonate, ethylene carbonate, methylene carbonate, fluoroethylene carbonate, trifluoromethylethylene carbonate, bisfluoroethylene carbonate and the compound shown in the following structural formula 2: ; Structural formula 2 In the structural formula 2 shown, R 21 , R 22 , R 23 , R 24 , R 25 , R 26 Each is independently selected from a hydrogen atom, a halogen atom, and a C1-C5 group.
[0024] In some preferred embodiments, the compound represented by structural formula 2 includes at least one of the following compounds 2-1 to 2-6: Compound 2-1 Compound 2-2 Compound 2-3 Compound 2-4 Compound 2-5 Compound 2-6.
[0025] In some preferred embodiments, the phosphate compound includes at least one of the compounds shown in the following structural formula 3: ; Structural formula 3 In the structural formula 3, R 31 , R 32 , R 33 Each independently selected from a C1-C5 saturated hydrocarbon group, an unsaturated hydrocarbon group, a halogenated hydrocarbon group, -Si(C m H 2m+1 )3, m is a natural number of 1 to 3; more preferably, the compound shown in the structural formula 3 includes at least one of tris(trimethylsilane) phosphate, tris(triethylsilane) phosphate, tripropargyl phosphate, dipropargyl methyl phosphate, dipropargyl ethyl phosphate, dipropargyl propyl phosphate, dipropargyl trifluoromethyl phosphate, dipropargyl-2,2,2-trifluoroethyl phosphate, dipropargyl-3,3,3-trifluoropropyl phosphate, dipropargyl hexafluoroisopropyl phosphate, triallyl phosphate, diallyl methyl phosphate, diallyl ethyl phosphate, diallyl propyl phosphate, diallyl trifluoromethyl phosphate, diallyl-2,2,2-trifluoroethyl phosphate, diallyl-3,3,3-trifluoropropyl phosphate and diallyl hexafluoroisopropyl phosphate.
[0026] In some preferred embodiments, the borate ester compound includes at least one of tris(trimethylsilyl)borate and tris(triethylsilyl)borate.
[0027] Specifically, in some embodiments of the present invention, based on the total mass of the non-aqueous electrolyte as 100%, the content of the auxiliary additive is 0.01% to 10%. Preferably, the content is 0.1% to 5%; more preferably, the content is 0.1% to 2%. Specifically, the content of any one of the optional substances in the auxiliary additive can be 0.01%, 0.05%, 0.08%, 0.1%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.2%, 2.5%, 2.8%, 3%, 3.2%, 3.5%, 3.8%, 4%, 4.5%, 5% or a range consisting of any two of these values.
[0028] Specifically, in some embodiments of the present invention, the lithium salt includes LiPF6, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, LiPO2F2, LiBF4, LiBOB, LiSbF6, LiAsF6, LiCF3SO3, LiDFOB, LiDFOP, LiN(SO2CF3)2, LiC(SO2CF3)3, LiN(SO2C2F5)2, LiCl, LiBr, LiI, LiClO4, LiB 10 Cl 10 , LiAlCl4, lithium chloroborane, and lithium tetraphenylborate.
[0029] Specifically, in some embodiments of the present invention, the negative electrode sheet includes a negative electrode material layer containing a negative electrode active material, and the negative electrode active material is any one or more of a silicon-based material and a carbon material. The silicon-based material is selected from one or more of a silicon material, a silicon oxide material, a silicon-carbon material, and a silicon alloy material; preferably, the silicon material is a nano-silicon material; preferably, the silicon oxide material is SiO x Material, wherein 0≤x<2; preferably, the silicon-carbon material is: a silicon-based material containing silicon and carbon materials, and / or a silicon-based material containing SiO y and a silicon-based material of a carbon material, wherein 0≤y<2; preferably, the silicon alloy material is a Mg2Si alloy material and / or a Fe2Si alloy material. The carbon material is selected from one or more of artificial graphite, natural graphite, composite graphite, graphene, and hard carbon; preferably, the carbon material is an artificial graphite material.
[0030] Specifically, in some embodiments of the present invention, the negative electrode material layer further includes a negative electrode binder, a negative electrode conductor and a negative electrode current collector. The material of the negative electrode current collector may be the same as that of the positive electrode current collector, which will not be described in detail here. The negative electrode binder and the negative electrode conductor may be the same as the positive electrode binder and the positive electrode conductor, respectively, which will not be described in detail here.
[0031] Specifically, in some embodiments of the present invention, the lithium-ion battery further includes a diaphragm, and the diaphragm is located between the positive electrode and the negative electrode.
[0032] The separator is an existing conventional separator, selected from one or more of a ceramic separator, a polymer separator, a non-woven fabric, and an inorganic-organic composite separator, for example, a single-layer polypropylene (PP) separator, a single-layer polyethylene (PE) separator, a double-layer PP / PE separator, a double-layer PP / PP separator, or a triple-layer PP / PE / PP separator.
[0033] The lithium ion battery of the present invention uses any one of compounds 1 to 5 as the first additive, fluoroethylene carbonate as the second additive, and the short-chain carboxylic acid ester compound represented by structural formula 1 as the solvent, and defines the mass percentage content of the first additive in the non-aqueous electrolyte a%, the mass percentage content of the second additive in the electrolyte b%, the mass percentage content of the compound represented by structural formula 1 in the non-aqueous electrolyte c%, and the specific surface area dm of the positive electrode material layer. 2 When the relationship between / g and the porosity e% of the positive electrode material layer satisfies 0.3≤0.01×(c+e+5d) / (a+b)≤20, 0.01≤a≤3, 0.05≤b≤1.5, 30≤c≤50, 6≤d≤12, and 10≤e≤35, a layer of organic protective film can be generated on the surface of the negative electrode to prevent the carboxylate from degrading the high temperature performance of the battery, and at the same time significantly improve the ionic conductivity of the electrolyte, thereby obtaining a lithium ion battery with better high temperature storage performance and fast charging cycle performance. DETAILED DESCRIPTION
[0034] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention.
[0035] Example 1
[0036] The method for preparing a lithium-ion battery in this embodiment comprises the following steps: (1) Preparation of non-aqueous electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and ethyl acetate (EA) are mixed, and then lithium hexafluorophosphate (LiPF6) is added to a molar concentration of 1.1 mol / L, and then compound 1 is added as the first additive, vinylene carbonate (VC), and fluoroethylene carbonate (FEC). Based on the total weight of the non-aqueous electrolyte as 100%, the content of the additive satisfying structural formula 1 is 0.05%, the content of VC is 3%, the content of FEC is 0.7%, and the content of ethyl acetate (compound 1-2) is 30%.
[0037] (2) Preparation of positive electrode sheet: The positive electrode active material LiFePO4, conductive carbon black Super-P and binder polyvinylidene fluoride (PVDF) were mixed in a mass ratio of 96:2:2, and then dispersed in N-methyl-2-pyrrolidone (NMP) to obtain a positive electrode slurry. The slurry was evenly coated on both sides of the aluminum foil current collector, dried, rolled, vacuum dried, and welded with an ultrasonic welder to obtain a positive electrode sheet. The specific surface area of the positive electrode material layer is 8 m 2 / g, and the porosity of the positive electrode material layer is 23%.
[0038] (3) Preparation of negative electrode sheet: The negative electrode active material artificial graphite, conductive carbon black Super-P, binder styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC) were mixed in a mass ratio of 95:1:1.5:2.5. Then they were dispersed in deionized water to obtain negative electrode slurry. The slurry was coated on both sides of the copper foil, dried, rolled, vacuum dried, and welded with nickel lead wires using an ultrasonic welder to obtain the negative electrode sheet.
[0039] (4) Preparation of battery cells: A three-layer separator with a thickness of 20 μm was placed between the positive plate and the negative plate, and then the sandwich structure consisting of the positive plate, the negative plate and the separator was wound. The wound body was flattened and placed in an aluminum foil packaging bag, and vacuum-baked at 85°C for 48 hours to obtain a battery cell to be injected with liquid.
[0040] (5) Battery filling and formation: In a glove box where the moisture and oxygen content are controlled below 10 ppm, the non-aqueous electrolyte prepared above is injected into the battery cell, vacuum packaged, and left to stand at 45°C for 48 hours. Then, the conventional formation of the first charge is carried out according to the following steps: 0.05C constant current charging for 2 hours, 0.1C constant current charging for 1 hour, and 0.2C constant current charging for 1 hour.
[0041] (6) Cell capacity division: The battery cell was left at 45°C for 48h, then vacuum sealed for a second time to remove the generated gas, then charged to 3.65V at a constant current of 0.2C, then charged at a constant voltage until the current dropped to 0.05C, and after being left for 5min, discharged to 2.5V at a constant current of 0.2C to obtain a lithium iron phosphate positive electrode / graphite negative electrode lithium ion battery.
[0042] Example 2 to Example 33 and Comparative Example 1 to Comparative Example 17 This embodiment and comparative example are used to compare and illustrate the lithium ion battery disclosed in the present invention, including most of the operating steps in the above-mentioned embodiment 1, and the differences are: the type of positive electrode active material, the composition of the non-aqueous electrolyte and the content of each component, the specific surface area and porosity of the positive electrode material, as shown in Tables 1 to 5.
[0043] The lithium-ion batteries prepared in the examples and comparative examples were subjected to the following performance tests: (1) High temperature storage performance test At 25°C, charge the battery to 3.65V (cut-off current 0.05C) with 1C constant current and constant voltage, and discharge it to 2.5V with 1C constant current, and record the discharge capacity of the battery. Then charge the battery to 3.65V (cut-off current 0.05C) with 1C constant current and constant voltage, and place it in a 60°C oven. Take it out after 30 days, and after the battery cools down, discharge it to 2.5V with 1C constant current at 25°C, and record the discharge capacity and volume of the battery.
[0044] High temperature storage capacity retention rate (%) = discharge capacity after 30 days storage at 60°C / discharge capacity before storage × 100% (2) Normal temperature fast charging cycle life test At 25°C, charge the battery with a 4C constant current until the battery is at 80% SOC, then charge it with a 1C constant current and constant voltage to 3.65V (cut-off current 0.05C), and then discharge it with a 1C constant current to 2.5V. Use this process to continuously perform cyclic charge and discharge tests, and record the discharge capacity of each cycle.
[0045] Cycle capacity retention rate (%) = current cycle discharge capacity / first cycle discharge capacity × 100% The capacity retention rate was recorded after 800 cycles.
[0046] (3) High temperature fast charging cycle life test At 45°C, charge the battery with a 4C constant current until the battery is at 80% SOC, then charge it with a 1C constant current and constant voltage to 3.65V (cut-off current 0.05C), and then discharge it with a 1C constant current to 2.5V. Use this process to continuously perform cyclic charge and discharge tests, and record the discharge capacity of each cycle.
[0047] Cycle capacity retention rate (%) = current cycle discharge capacity / first cycle discharge capacity × 100% The capacity retention rate was recorded after 800 cycles.
[0048] Test Results As shown in Table 1, various parameters of the lithium ion batteries prepared in Examples 1 to 20 and Comparative Examples 1 to 14 are shown; the differences between Examples 2 to 20 and Comparative Examples 1 to 14 and Example 1 are the relevant parameters in Table 1.
[0049] Table 1 Group First additive content a / % Second additive content b / % Solvent content c / % <![CDATA[Specific surface area of the positive electrode material layer / d / m 2 / g]]> Porosity of positive electrode material layer e / % 0.01×(c+e+5d) / (a+b) Capacity retention rate after 30-day storage at 60°C / % 25℃ 4C / 1C cycle 800 weeks capacity retention rate / % 45℃ 4C / 1C cycle 800 weeks capacity retention rate / % Example 1 0.05 0.7 30 8 23 1.42 82.5 93.4 88.6 Example 2 0.08 0.6 35 8 15 1.32 81.2 91.3 83.2 Example 3 0.1 0.4 37 7 20 1.84 81.6 93.1 84.4 Example 4 0.3 0.1 40 7 10 2.13 82.3 91.9 83.7 Example 5 0.7 0.8 43 9 27 0.77 82.9 94.3 90.2 Example 6 1 1 45 10 30 0.63 83.7 93.8 90.6 Example 7 1 1 30 10 20 0.50 84.5 91.6 89.4 Example 8 0.01 0.3 32 7 13 2.58 75.3 90.4 80.5 Example 9 0.06 0.05 33 9 17 8.64 73.8 91.1 79.7 Example 10 0.07 0.5 47 10 29 2.21 74.6 91.8 83.9 Embodiment 11 0.09 0.7 38 11 27 1.52 76.8 91.4 83.6 Example 12 0.3 0.9 44 7 33 0.93 81.8 89.5 82.4 Example 13 0.03 0.08 36 10 24 10.00 72.3 86.6 80.3 Embodiment 14 0.6 1.5 50 12 26 0.65 81.5 85.9 83.4 Embodiment 15 0.8 0.06 36 6 31 1.13 76.1 89.5 85.6 Example 16 0.9 0.07 48 12 35 1.47 73.2 90.7 84.1 Embodiment 17 3 0.05 49 7 34 0.39 85.1 86.4 81.5 Embodiment 18 0.02 0.06 46 12 10 14.50 71.2 84.2 76.5 Embodiment 19 0.01 0.05 35 10 35 20.00 72.5 85.6 77.8 Embodiment 20 1 1 30 6 10 0.35 84.8 88.5 78.9 Comparative Example 1 0 0.1 30 7 10 7.50 65.7 80.6 70.3 Comparative Example 2 0.05 0 30 7 10 15.00 66.5 81.7 72.4 Comparative Example 3 0.008 0.1 30 7 10 6.94 66.9 80.8 70.8 Comparative Example 4 3.2 0.5 40 10 30 0.32 78.2 83.6 74.9 Comparative Example 5 0.5 0.03 30 7 10 1.42 73.3 84.8 73.8 Comparative Example 6 0.8 1.2 35 8 20 0.48 76.6 85.1 74.6 Comparative Example 7 0.6 0.5 28 8 25 0.85 79.8 83.2 75.6 Comparative Example 8 0.5 0.4 52 10 25 1.41 71.6 86.3 71.6 Comparative Example 9 2 0.7 45 5 25 0.35 80.8 83.5 75.3 Comparative Example 10 0.01 0.7 45 13 25 1.90 71.4 86.3 72.5 Comparative Example 11 0.09 0.05 45 9 4 6.71 70.3 83.9 75.6 Comparative Example 12 0.08 0.08 45 9 36 7.88 68.5 84.5 74.2 Comparative Example 13 0.01 0.05 30 12 35 20.83 66.8 81.2 70.8 Comparative Example 14 3 1 30 6 35 0.24 78.6 79.5 72.3 It can be seen from the test results of Examples 1 to 20 and Comparative Examples 1 to 14 that the lithium ion battery provided in the present invention uses at least one compound of Compounds 1 to 5 as the first additive, fluoroethylene carbonate as the second additive, and the compound represented by Structural Formula 1 as the solvent, and defines the mass percentage of the first additive in the electrolyte a%, the mass percentage of the second additive in the electrolyte b%, the mass percentage of the compound represented by Structural Formula 1 in the non-aqueous electrolyte c%, and the specific surface area dm of the positive electrode material layer. 2 When the relationship between / g and the porosity e% of the positive electrode material layer satisfies 0.3≤0.01×(c+e+5d) / (a+b)≤20, 0.01≤a≤3, 0.05≤b≤1.5, 30≤c≤50, 6≤d≤12, 10≤e≤35, a lithium ion battery with excellent high temperature storage performance and fast charging cycle performance can be obtained.
[0050] From the test results of Examples 1 to 20 and Comparative Examples 1 to 14, it can be seen that when the mass percentage of the first additive in the electrolyte is a%, the mass percentage of the second additive in the electrolyte is b%, the mass percentage of the compound represented by the structural formula 1 in the non-aqueous electrolyte is c%, and the specific surface area dm of the positive electrode material layer is 2 If any of the parameters of / g and the porosity e% of the positive electrode material layer does not meet the range or the value of the relationship 0.01×(c+e+5d) / (a+b) is too large or too small, it is impossible to ensure that a layer of organic protective film can be formed on the surface of the negative electrode, so that the negative electrode and the carboxylic acid ester will react with each other, causing the carboxylic acid ester to deteriorate the high-temperature performance of the battery. In addition, it is impossible to improve the lithium ion transmission and charge transfer efficiency at the electrode-electrolyte interface, and it is impossible to improve the fast charging cycle performance of the battery.
[0051] When the mass percentage of the first additive in the electrolyte is a%, the mass percentage of the second additive in the electrolyte is b%, the mass percentage of the compound represented by the structural formula 1 in the non-aqueous electrolyte is c%, and the specific surface area dm of the positive electrode material layer is2 When the value of the porosity e% of the positive electrode material layer further satisfies 0.5≤0.01×(c+e+5d) / (a+b)≤10, 0.05≤a≤1, 0.1≤b≤1, 30≤c≤45, 7≤d≤10, and 10≤e≤30, a dense and thin organic protective film with certain flexibility can be better formed during the battery formation process, and the carboxylic acid ester can be better prevented from degrading the high temperature performance of the battery. Within this range, the positive electrode material layer also obtains the contact area with the electrolyte as much as possible, which is beneficial to the adsorption and infiltration of the electrolyte by the electrode piece, improves the liquid retention of the battery cell, ensures that the lithium ion transmission and charge transfer efficiency of the electrode-electrolyte interface is improved at a high current density during high rate charging, and is beneficial to further improve the fast charge cycle performance of the battery, thereby obtaining a lithium ion battery that takes into account both excellent high temperature storage performance and fast charge cycle performance.
[0052] Table 2 shows various parameters of the lithium-ion batteries prepared in Example 1 and Examples 21 to 24; the differences between Examples 21 to 24 and Example 1 lie in the relevant parameters in Table 2.
[0053] Table 2
[0054] From the measurement results in Table 2, it can be seen that when the mass percentage of the first additive is a%, the mass percentage of the second additive in the electrolyte is b%, the mass percentage of the compound represented by the structural formula 1 in the non-aqueous electrolyte is c%, and the specific surface area dm of the positive electrode material layer is 2 / g and the porosity e% of the positive electrode material layer and the value of the relationship 0.01×(c+e+5d) / (a+b) meet the relevant requirements, adding compound 1 to compound 5 as the first additive can optimize the high temperature storage performance and fast charging cycle performance of the lithium-ion battery, indicating that the battery system of the present invention is universal for different first additives.
[0055] Table 3 shows various parameters of the lithium-ion batteries prepared in Example 1, Example 25 to Example 29 and Comparative Examples 15 to Comparative Example 17; the differences between Example 25 to Example 29 and Comparative Examples 15 to Comparative Example 17 and Example 1 are the relevant parameters in Table 3.
[0056] Table 3
[0057] As shown in Table 3, when the mass percentage of the first additive is a%, the mass percentage of the second additive in the electrolyte is b%, the mass percentage of the compound represented by the structural formula 1 in the non-aqueous electrolyte is c%, and the specific surface area dm of the positive electrode material layer is 2 / g and the porosity e% of the positive electrode material layer and the value of the relationship 0.01×(c+e+5d) / (a+b) meet the relevant high requirements, adding different types of solvents shown in structural formula 1 can achieve the optimization of the high temperature storage performance and fast charge cycle performance of the lithium-ion battery, indicating that the battery system of the present invention is universal for different solvents. It can be seen from the test results of Example 1, Example 25 to Example 29 and Comparative Examples 15 to Comparative Examples 17 that if a long-chain carboxylic acid ester compared with the second additive is used, the viscosity is larger and the effect of improving the fast charge cycle performance of the battery is not good.
[0058] Table 4 shows various parameters of the lithium-ion batteries prepared in Example 1 and Examples 30 to 34; the differences between Examples 30 to 34 and Example 1 lie in the relevant parameters in Table 4.
[0059] Table 4
[0060] As shown in Table 4, when the mass percentage of the first additive is a%, the mass percentage of the second additive in the electrolyte is b%, the mass percentage of the compound represented by the structural formula 1 in the non-aqueous electrolyte is c%, and the specific surface area dm of the positive electrode material layer is 2 / g and the porosity e% of the positive electrode material layer and the value of the relationship 0.01×(c+e+5d) / (a+b) meet the relevant requirements, different types of positive electrode active materials can be used to optimize the high temperature storage performance and fast charging cycle performance of lithium-ion batteries, indicating that the battery system of the present invention is universal for different positive electrode active materials.
[0061] Table 5 shows various parameters of the lithium-ion batteries prepared in Example 1 and Examples 35 to 37; the differences between Examples 35 to 37 and Example 1 lie in the relevant parameters in Table 5.
[0062] Table 5
[0063] Wherein: VC-vinylene carbonate, DTD-vinyl sulfate, MMDS-methylene methanedisulfonate, TMSP-tri(trimethylsilyl)phosphate.
[0064] From the measurement results in Table 5, it can be seen that when the mass percentage of the first additive is a%, the mass percentage of the second additive in the electrolyte is b%, the mass percentage of the compound represented by the structural formula 1 in the non-aqueous electrolyte is c%, and the specific surface area dm of the positive electrode material layer is 2 / g and the porosity e% of the positive electrode material layer and the value of the relationship 0.01×(c+e+5d) / (a+b) meet the relevant high requirements, adding different auxiliary additives can optimize the high temperature storage performance and fast charging cycle performance of the lithium-ion battery, indicating that the battery system of the present invention is universal for different positive electrode active materials.
[0065] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A lithium ion battery, characterized in that: Including positive electrode sheet, negative electrode sheet and non-aqueous electrolyte; The positive electrode sheet includes a positive electrode material layer, the positive electrode material layer includes a positive electrode active material, and the positive electrode active material includes a phosphate compound LiFe 1-x-y Mn x M y PO4, wherein 0≤x≤0.8, 0≤y≤0.05, and M includes any one or more of Co, B, Ga, F, W, Zr, Mg, Na, Pb, K, Al, Cr, Ba, Ca, Ni, Sr, Ti, Zn, Si, V, Mo, or Nb; The non-aqueous electrolyte comprises a first additive, a second additive, a lithium salt and a solvent; the first additive comprises at least one of the following compounds: Compound 1 Compound 2 Compound 3 Compound 4 Compound 5; The second additive includes fluoroethylene carbonate; The solvent includes a compound shown in structural formula 1; ; Structural formula 1 Wherein, R1 is an alkyl group or a fluoroalkyl group having a carbon number ≤ 2, R2 is an alkyl group having a carbon number ≤ 3, and the total number of carbon atoms in R1 and R2 is ≤ 4; The lithium-ion battery meets the following conditions: 0.3≤0.01×(c+e+5d) / (a+b)≤20, 0.01≤a≤3, 0.05≤b≤1.5, 30≤c≤50, 6≤d≤12, 10≤e≤35; Wherein, a is the mass percentage of the first additive in the non-aqueous electrolyte, in units of %; b is the mass percentage of the second additive in the non-aqueous electrolyte, unit is %; c is the mass percentage of the compound represented by structural formula 1 in the non-aqueous electrolyte, in units of %; d is the specific surface area of the positive electrode material layer, in m 2 / g; e is the porosity of the positive electrode material layer, in %.
2. The lithium-ion battery according to claim 1, characterized in that The lithium ion battery satisfies: 0.5≤0.01×(c+e+5d) / (a+b)≤10.
3. The lithium ion battery according to claim 1, characterized in that The mass percentage a% of the first additive in the non-aqueous electrolyte is 0.05%-1%.
4. The lithium ion battery according to claim 1, characterized in that The mass percentage b% of the second additive in the non-aqueous electrolyte is 0.1%-1%.
5. The lithium ion battery according to claim 1, characterized in that The mass percentage c% of the compound represented by structural formula 1 in the non-aqueous electrolyte is 30% to 45%.
6. The lithium ion battery according to claim 1, characterized in that The specific surface area d of the positive electrode material layer is 7 m 2 / g~10m 2 / g.
7. The lithium ion battery according to claim 1, characterized in that The porosity e% of the positive electrode material layer is 10% to 30%.
8. The lithium ion battery according to claim 1, characterized in that The compound represented by the structural formula 1 includes at least one of the following compounds 1-1 to 1-6: Compound 1-1 Compound 1-2 Compound 1-3 Compound 1-4 Compound 1-5 Compounds 1-6.
9. The lithium ion battery according to claim 1, characterized in that The non-aqueous electrolyte further includes an auxiliary additive, wherein the auxiliary additive includes at least one of a cyclic sulfate compound, a sultone compound, a cyclic carbonate compound, a phosphate compound and a borate compound; and / or, Based on the total mass of the non-aqueous electrolyte being 100%, the content of the auxiliary additive is 0.01% to 10%.
10. The lithium ion battery according to claim 9, characterized in that The cyclic sulfate ester compound includes at least one of 4-methylvinyl sulfate, vinyl sulfate, and propylene sulfate; and / or, The sultone compound includes at least one of 1,3-propane sultone, 1,4-butane sultone and propenyl-1,3-sultone; and / or, The cyclic carbonate compound includes at least one of vinylene carbonate, ethylene carbonate, methylene carbonate, fluoroethylene carbonate, trifluoromethylethylene carbonate, bisfluoroethylene carbonate and the compound shown in the following structural formula 2: ; Structural formula 2 In the structural formula 2 shown, R 21 , R 22 , R 23 , R 24 , R 25 , R 26 Each is independently selected from a hydrogen atom, a halogen atom, a C1-C5 group; and / or, The phosphate compound includes at least one of the compounds shown in the following structural formula 3: ; Structural formula 3 In the structural formula 3, R 31 , R 32 , R 33 Each independently selected from a C1-C5 saturated hydrocarbon group, an unsaturated hydrocarbon group, a halogenated hydrocarbon group, -Si(C m H 2m+1 )3, m is a natural number from 1 to 3; and / or, The borate ester compound includes at least one of tris(trimethylsilyl)borate and tris(triethylsilyl)borate.
Citation Information
Patent Citations
Lithium secondary battery and electric device
CN117280511A
Battery
CN118281343A
Nonaqueous electrolyte battery, battery pack, and automobile
JP2008186803A
Cited By
Lithium-ion battery
WO2026179346A1